2016
DOI: 10.1007/s11064-016-1858-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic (3-Weeks) Treatment of Estrogen (17β-Estradiol) Enhances Working and Reference Memory in Ovariectomized Rats: Role of Acetylcholine

Abstract: Recently there has been a growing interest in the effects of estrogen on cognitive functions. In this study, we aimed to examine 17β-estradiol treatment on working and reference memory in ovariectomized rats. We also examined the changes in the acetylcholine (ACh) levels in the brain areas associated with learning and memory. The study was performed on Sprague-Dawley type 3-month-old female rats. The rats were divided into four groups as control, ovariectomy (OVX), and OVX and estrogen treatment (10 µg/day i.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Estrogen prevents aberrant hippocampal neuronal apoptosis and cognitive deficits (Sales et al 2010, Uzum et al 2016, Yazgan & Naziroglu 2017, and the present study establishes the contribution of a controlled autophagy mechanism in estrogen-mediated neuroprotection. Here, we essentially demonstrated that estrogen deficiency up-regulates the expression of autophagy proteins such as Beclin1, LC3 and ATG7 along with the levels of ATG5/ATG12 conjugate within the hippocampus, indicative of an estrogen-regulated phagophore elongation and association with the autophagic vesicles.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Estrogen prevents aberrant hippocampal neuronal apoptosis and cognitive deficits (Sales et al 2010, Uzum et al 2016, Yazgan & Naziroglu 2017, and the present study establishes the contribution of a controlled autophagy mechanism in estrogen-mediated neuroprotection. Here, we essentially demonstrated that estrogen deficiency up-regulates the expression of autophagy proteins such as Beclin1, LC3 and ATG7 along with the levels of ATG5/ATG12 conjugate within the hippocampus, indicative of an estrogen-regulated phagophore elongation and association with the autophagic vesicles.…”
Section: Discussionsupporting
confidence: 72%
“…Correspondingly, ovarian failure and estrogen deficiency, which characterize menopause in women, suppress cerebral ER levels (Qu et al 2013, Fang et al 2018 and alter neuronal functions, including cognition (Kim et al 2016, Djiogue et al 2018. Estrogen deficiency induces hippocampal apoptosis, neuronal loss (Sales et al 2010, Yazgan & Naziroglu 2017 and cognitive dysfunctions (Kim et al 2016, Djiogue et al 2018, while estradiol therapy reduces apoptosis and improves learning-memory performances (Sales et al 2010, Uzum et al 2016, Yazgan & Naziroglu 2017. However, the underlying mechanisms remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it has been revealed that oestrogens have critical beneficial effects in addition to reproduction. For instance, adult female rats which received 10 μg day −1 17β‐oestradiol for 3 weeks demonstrated enhanced working and reference memory (Uzum et al, ). Another study suggests oestrogens could attenuate disease‐associated cognitive deficits and reduce Alzheimer's disease risk (Engler‐Chiurazzi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that ovariectomy may induce cognitive dysfunction in young (13)(14)(15)(16) and also in middle-aged rats (29,30,43), while estrogens may improve learning and memory performance following ovariectomy in both, young (15,24,(59)(60)(61) and middle-aged females (21-23, 25, 29, 31). However, OVX females in our experiment exhibited mild memory impairment only, and the estradioltreated group did not outperform vehicle-treated OVX rats.…”
Section: Discussionmentioning
confidence: 99%